Neglected Tropical Disease in Nigeria: Implication for Health Education - Ngozika, Ojide (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
This work looked at neglected tropical diseases in Nigeria; implication for health Education. The paper saw neglected tropical diseases as a medically diverse group of tropical infections which are especially common in low-income populations in developing regions of Africa, Asia, and the Americas. They are caused by a variety of pathogens such as viruses, bacteria, protozoa and helminthes, unsafe water, poor housing conditions and poor sanitation. It is neglected because government at the three tier level is not interested in such diseases and many people do not see it as priority to control it through prevention or by therapeutic method, health educators have not created enough information or awareness about those diseases for the population to become conscious of it and health agencies like WHO, UNICEF, USAID, Center for disease control (CDC), the Cater Center (TCC) have little report about such diseases in Nigeria. There are 17 different types of these neglected tropical diseases identified by WHO. Seven of these diseases are mostly affecting Nigerian but six were addressed with their implications for health education in this paper. They are lymphatic filariasis, onchocerciasis, schistosomiasis, and three soil-transmitted helminth infections (hookworm, ascariasis and trichuriasis). The implication of this study is that health educators should arise and create awareness in these diseases in order to improve health status of people at the endemic areas through organizing seminar/workshop to educate communities on the preventive measures and early detection of the neglected tropical diseases.